2010
DOI: 10.1074/jbc.m110.111559
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Cinaciguat (BAY 58–2667) Bound to Nostoc H-NOX Domain Reveals Insights into Heme-mimetic Activation of the Soluble Guanylyl Cyclase

Abstract: Heme is a vital molecule for all life forms with heme being capable of assisting in catalysis, binding ligands, and undergoing redox changes. Heme-related dysfunction can lead to cardiovascular diseases with the oxidation of the heme of soluble guanylyl cyclase (sGC) critically implicated in some of these cardiovascular diseases. sGC, the main nitric oxide (NO) receptor, stimulates second messenger cGMP production, whereas reactive oxygen species are known to scavenge NO and oxidize/inactivate the heme leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
2
4

Year Published

2012
2012
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(136 citation statements)
references
References 28 publications
7
123
2
4
Order By: Relevance
“…sGC is the third protein whose heme insertion has now been found to be hsp90-dependent (the others are iNOS and neuronal NOS) (30,31). Given that sGC and NOS enzymes have markedly different protein structures and heme environments (37,38), our findings suggest that hsp90 may have a more general role in heme protein maturation than was previously realized. In the present study, hsp90 associated most strongly with aposGC-β1 in cells and the association weakened or fell apart when heme had become inserted.…”
Section: Discussioncontrasting
confidence: 46%
“…sGC is the third protein whose heme insertion has now been found to be hsp90-dependent (the others are iNOS and neuronal NOS) (30,31). Given that sGC and NOS enzymes have markedly different protein structures and heme environments (37,38), our findings suggest that hsp90 may have a more general role in heme protein maturation than was previously realized. In the present study, hsp90 associated most strongly with aposGC-β1 in cells and the association weakened or fell apart when heme had become inserted.…”
Section: Discussioncontrasting
confidence: 46%
“…Although these structural changes help to show how sGC-␤1 may achieve a catalytically-active state in response to NO binding to the sGC-␤1 heme, these particular structural changes are unlikely to be the ones that weaken the apo-sGC-␤1 interaction with hsp90 because we know that heme insertion into aposGC-␤1 alone, without any NO or sGC activation, is sufficient to weaken its hsp90 association (14). However, the same subset of structural changes (21,26) is possibly associated with the process that led to a M r redistribution of sGC-␤1 in the cells. Thus, BAY 60-2770 may promote extensive protein conformational changes within apo-sGC-␤1 that lead to hsp90 dissociation, sGC-␤1 redistribution in cells, and activation of sGC enzy- FIGURE 8.…”
Section: Discussionmentioning
confidence: 99%
“…Structural Insights-The crystal structures of the Nostoc H-NOX domain are regarded to be good models of the mammalian sGC-␤1 regulatory domain structure (21,26), whose structure remains to be solved. In comparing the structures of a H-NOX domain containing bound BAY 58-2667 or BAY 60-2770 with that of the drug free, heme-containing form, the authors (21, 26) identified some specific structural changes that occur with drug binding, that mainly involve the ␣-F helix and flanking residues that are located proximal to the bound heme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the Fe 2ϩ -His bond cleavage necessarily triggers structural changes within the dimeric protein, mediated by interactions between subunits. In the absence of three-dimensional crystal structure of heterodimeric sGC, the heme domain of the ␤-subunit was modeled from the structure of homologous bacterial NO sensors (8 -10), and several studies used these sensors as structural models for sGC (11,12), albeit their exact physiological role remains to be determined (13).…”
Section: ؊1 ⅐Smentioning
confidence: 99%